A War in the Distance : Ukraine and the Return of History. - Degot, Ekaterina; Steirischer Herbst Graz 2022; Riff, David (Berlin : Hatje Cantz, 2023)
With contributions by Keti Chukhrov, Maja Haderlap, Dana Kavelina, Olexii Kuchanskyi, Michael Marder, Boris Nikitin, Martin Pollack, Syargey Prylutsky, Galina Rymbu, Marcia Sá Cavalcante Schuback, Ostap Slyvynsky, Oxana Timofeeva
Published in conjunction with steirischer herbst festival '22, A War in the Distance, September 22 - October 16, 2022, Graz, Styria, Austria
boek
Keywords: Oekraïne